The female ancestor's tale: Long‐term matrilineal continuity in a nonisolated region of Tuscany. Issue 3 (6th September 2018) - Leonardi, Michela; Sandionigi, Anna; Conzato, Annalisa; Vai, Stefania; Lari, Martina; Tassi, Francesca; Ghirotto, Silvia; Caramelli, David; Barbujani, Guido
Abstract: Objectives: With the advent of ancient DNA analyses, it has been possible to disentangle the contribution of ancient populations to the genetic pool of the modern inhabitants of many regions. Reconstructing the maternal ancestry has often highlighted genetic continuity over several millennia, but almost always in isolated areas. Here we analyze North‐western Tuscany, a region that was a corridor of exchanges between Central Italy and the Western Mediterranean coast. Materials and methods: We newly obtained mitochondrial HVRI sequences from 28 individuals, and after gathering published data, we collected genetic information for 119 individuals from the region. Those span five periods during the last 5, 000 years: Prehistory, Etruscan age, Roman age, Renaissance, and Present‐day. We used serial coalescent simulations in an approximate Bayesian computation framework to test for continuity between the mentioned groups. Results: Our analyses always favor continuity over discontinuity for all groups considered, with the Etruscans being part of the genealogy. Moreover, the posterior distributions of the parameters support very small female effective population sizes. Conclusions: The observed signals of long‐term genetic continuity and isolation are in contrast with the history of the region, conquered several times (Etruscans, Romans, Lombards, and French). While the Etruscans appear as a local population, intermediate between the prehistoric and the other samples, we suggest that the other conquerors—arriving from far—had a consistent social or sex bias, hence only marginally affecting the maternal lineages. At the same time, our results show that long‐term genealogical continuity is not necessarily linked to geographical isolation.